Choroidal Osteoma with Choroidal Neovascular Membrane treated with Anti- vascular Endothelial Growth Factor: A Rare Case with Review of Literatures - Dorji, Phuntsho; Lepcha, Nor Tshering; Thapa, Raba (Nepalese Journal of Ophthalmology, 2021)
Introduction: Choroidal osteoma, usually unilateral, is a rare benign tumor of choroid. It is predominantly seen in young females. Case: We report a case of a 35-year-old female with unilateral choroidal osteoma associated with choroidal neovascular membrane (CNVM). The diagnosis was confirmed with clinical examination, ocular ultrasonography, fundus fluorescein angiography and macular optical coherence tomography. Choroidal neovascular membrane improved with 3 doses of bevacizumab, an anti-vascular endothelial growth factors (Anti-VEGF).Conclusion: Anti-VEGF monotherapy can be a cost effective primary modality of treatment for choroidal neovascular membrane secondary to choroidal osteoma.